Primary Spindle Cell Malignant Melanoma of Esophagus: An Unusual Finding - Rawandale, Nirmalkumar A. (J Clin Diagn Res, 2016)
Malignant melanoma of esophagus is usually a metastatic tumour rather than a primary tumour. Primary malignant melanoma accounts for less than 0.2% of all esophageal neoplasm. We report a case of primary spindle cell malignant melanoma of esophagus in a 69-year-old male who presented with history of dysphagia since 1 month. Radiological examinations revealed polypoidal growth at lateral aspect of esophagus. Biopsy was reported as grade III squamous cell carcinoma. Video assisted thoracoscopic esophagectomy was performed. Histopathological examination along with immunohistochemistry gave confirmed diagnosis of primary spindle cell malignant melanoma of esophagus. Though a rare entity, due to its aggressive nature and poor prognosis primary malignant melanoma should be one of the differential diagnoses in a patient with polypoidal esophageal mass lesion. Despite radical surgical treatment prognosis is extremely poor.